Bone augmentation with autologous tooth shell in the esthetic zone for dental implant restoration: a pilot study - Shuyi Li; Ming Gao; Miao Zhou; Yibo Zhu (International Journal of Implant Dentistry, 2021)
Abstract Objectives To investigate the outcome and short-term follow-up of autogenous tooth shell (TS) grafting for bone augmentation in the esthetic zone, as well as stability and esthetics of implant-supported restoration. Materials and methods A total of 8 patients with 11 implants in 11 sites were enrolled in this study. All the horizontal and/or vertical bone defects in the esthetic zone were augmented by tooth shells, which were fixed laterally to the residual bone with osteosynthesis screws. The gap between the shell and residual bone was filled with Bio-Oss® granules. Four months after bone augmentation, dimensionally sufficient dental implants were inserted and implants-supported prostheses were made 3 months later. The esthetic outcome was evaluated by pink esthetic score (PES) and white esthetic score (WES) one year after prosthetic restoration. Horizontal ridge width (HRW) was assessed before and immediately after bone augmentation, as well as 4 and 19 months post-augmentation by radiography. The stability and absorption of TS grafts were evaluated at the 4th and 19th months post-augmentation. Results Though wound dehiscences occurred in 3 cases, secondary healings were obtained after TS modification and irrigation. The other 5 cases went through uneventful healing during the whole observation period. Radiographic examination showed that HRW was 8.01 ± 0.93 mm (median: 7.80, 95% CI 7.38, 8.64) 4 months after TS augmentation, which was statistically different compared to HRW (2.72 ± 1.73 mm) at the baseline. Mean HRW gain was 5.29 ± 2.03 mm (median: 4.60, 95% CI 3.92, 6.66). Three-dimensional bone volume in all the augmented sites was sufficient for dental implants insertion and prosthetic restoration. Follow-up of one year showed stable marginal bone around dental implants. The implant survival rate was 100%. HRW losses were 0.65 ± 0.43 mm (the 4th month) and 1.05 ± 0.54 mm (the 19th month) compared to HRW immediately after augmentation. The PES and WES of final prosthetic restorations were 8.09 ± 0.70 and 8.91 ± 0.54, respectively. Conclusions Autogenous tooth shell grafting is a reliable approach for bone augmentation in the esthetic zone for dental implant treatment, allowing for favorable stability and esthetic outcome of implant-supported prosthesis within the one-year follow-up period.